2014
DOI: 10.1166/jnn.2014.10113
|View full text |Cite
|
Sign up to set email alerts
|

Surface Plasmon Effect of Ag Nanodots Embedded in Amorphous Si Window Layers Deposited on Si Solar Cells

Abstract: We investigated solar cells containing temperature-dependent Ag nanodots embedded in an amorphous Si thin film layer by using hot-wire chemical vapor deposition in order to improve the properties of crystalline Si solar cells. An Ag thin film with a thickness of 10 nm was deposited by DC sputtering followed by annealing at various temperatures ranging from 250 to 850 degrees C for 15 min under N2 gas. As increasing the annealing temperature, the Ag nanodots were enlarged and the photoreflectances of the sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Ingle et al 4 showed that metallic nanoparticles (NPs) had a broad-spectrum antimicrobial activity due to their small size and high surface to volume ratio. Further, many NP types, such as silver, 5 copper iodide, 6 and titanium dioxide, 7 interacting with the bacterial cell membrane can inactivate bacterial cells and norovirus surrogates causing release of intracellular substances and cell death, 8 crippling the viral capsid possibly by denaturing its proteins. Few reports are available on antiviral activity of copper nanoparticles, which confirms that copper nanoparticles also possess promising antiviral activity.…”
Section: Introductionmentioning
confidence: 99%
“…Ingle et al 4 showed that metallic nanoparticles (NPs) had a broad-spectrum antimicrobial activity due to their small size and high surface to volume ratio. Further, many NP types, such as silver, 5 copper iodide, 6 and titanium dioxide, 7 interacting with the bacterial cell membrane can inactivate bacterial cells and norovirus surrogates causing release of intracellular substances and cell death, 8 crippling the viral capsid possibly by denaturing its proteins. Few reports are available on antiviral activity of copper nanoparticles, which confirms that copper nanoparticles also possess promising antiviral activity.…”
Section: Introductionmentioning
confidence: 99%